Oligomerization of PER2 as a dynamic mode of regulation of the mammalian circadian clock - Paulomi Sanyal; Diksha Sharma; Akhila Viswan; Priya Crosby; Vaishali Narayanan; Jackson Baumgartner; Carrie L. Partch; Ashok Sekhar (Proceedings of the National Academy of Sciences, 2026)
PER2 is a central transcriptional regulator in the mammalian circadian clock that closes the negative transcription–translation feedback loop by repressing its own transcription. The balance between the synthesis of PER2 and its degradation is a key factor that determines the circadian period. PER2 stability hinges on antagonistic phosphorylation events—phosphorylation at the familial advanced sleep phase site stabilizes PER2 while phosphorylation at the phosphodegron promotes degradation. The molecular mechanism by which phosphorylation elicits structural changes remains unclear, particularly because the phosphodegron is located in an intrinsically disordered region. Here, we show that the region encompassing the structured PER-ARNT-SIM (PAS) domains of PER2 and the downstream phosphodegron region form a large ~30 subunit homo-oligomer that resembles PER2 microbodies observed in mouse fibroblasts. Oligomerization is an emergent property that requires the cooperative interplay between the ordered PAS domains and the neighboring disordered segment. The phosphodegron is sequestered within this oligomer and inaccessible to Casein Kinase 1 (CK1). Intriguingly, Dark-state Exchange Saturation Transfer NMR experiments reveal that the oligomer coexists with dimeric PER2 and phosphorylation of the phosphodegron by CK1 occurs via this sparsely populated dimer. Using phosphomimetic variants, we then demonstrate that phosphorylation at the phosphodegron region destabilizes the oligomer. Our findings reveal the existence of structural polymorphism in PER2 and establish that oligomerization prevents CK1 from phosphorylating the phosphodegron, while phosphorylation of the dimer opposes oligomerization. This mutually antagonistic switch links structural assembly to posttranslational modifications and provides a mechanism by which phosphorylation tunes PER2 turnover and regulates circadian time-period.